Psychosocial functioning in schizophrenia: Are some symptoms or demographic characteristics predictors across the functioning domains? - Sirijit Suttajit (2018)
© 2015 Suttajit et al. This study aimed to examine symptoms/demographic characteristics as predictors for psychosocial functioning among individuals with schizophrenia. The Personal and Social Performance (PSP) scale was used to assess psychosocial functioning. Other measures of interest included were the Clinical Global Impression, Severity scale, and the Marder’s five-factor model of the Positive and Negative Syndrome Scale. This study included 199 participants with non-acute stage schizophrenia. Spearman correlation coefficients and stepwise multiple linear regression analyses were applied to determine the correlates and predictors of PSP domain/total scores. Younger age, earlier age of schizophrenia onset, severe illness, positive symptoms, negative symptoms, disorganized thought, hostility/excitement, and anxiety/depression were found to significantly correlate with poor functioning. Severe illness and negative symptoms are the main predictors of greater impairment of socially useful activities, personal and social relationships, and self-care. Further prospective studies in other settings, which would include an increased number of variables such as neurocognitive function and social support, are warranted.